Open tubular capillary column immobilized with sulfobutylether‐β‐cyclodextrin for chiral separation in capillary electrochromatography. Issue 10 (24th March 2021) - Zhou, Lifen; Lu, Yao; Sun, Genlin
Abstract: A novel chiral open tubular capillary column was fabricated with sulfobutylether‐β‐cyclodextrin and glycidyl methacrylate for enantioseparation in capillary electrochromatography. First, the pretreated silica‐fused capillary was treated with 3‐trimethoxysilyl propyl methacrylate to attach double bond ligand onto the surface. A copolymer layer was formed on the surface of capillary using glycidyl methacrylate and ethylene dimethacrylate by in situ one‐pot polymerization. Sulfobutylether‐β‐cyclodextrin was encapsulated inside the copolymerized layer. The morphology of the developed column was characterized by field emission scanning electron microscopy. The effect of organic percentage and pH value of the mobile phase on electroosmotic flow and resolution was also investigated. The performance of the fabricated column was validated by separation of amlodipine besilate, 2, 3‐diphenylpropionic acid, tropic acid, and pantoprazole enantiomers with good resolutions of 3.67, 4.82, 3.34, and 2.61, respectively. The repeatabilities of column‐to‐column and day‐to‐day through relative standard deviation were found better than 4%, exhibiting satisfactory repeatability of the developed column. The results reveal that open tubular capillary columns modified with β‐cyclodextrin show a great prospect for enantioseparation of chiral drugs in capillary electrochromatography.